BISAIN APP AS A SOLUTION OF SHARIA FUNDING FOR SMES IN INTEGRATED SYSTEM - Sharif, M A B M; Imron, M A (PEOPLE: International Journal of Social Sciences, 2019)
Indonesia has named as a country with the fourth largest population in the world, which reaching 267 million peoples. In fulfilling its economic activities, one of the Indonesian people’s businesses is opening a small and medium-sized business. In 2018, there were a number of Indonesian SMEs, which reached 59.2 million SMEs. Every SMEs actor needs a capital boost to proclaim his business. Besides that, investors also want to invest their money to make a profit. Since this very potential market, make a strong reason for the establishment of BisaIn App as an application that connects between SMEs actors and investors with sharia principles. With sharia principles, every transaction that is carried out will guarantee transactions that are transparent, safe, legal, profitable and lawful. The government through the Financial Services Authority (FSA) will also guarantee from every transaction for all parties. This App platform will also increase funding alternatives for developing SMEs business as well as supporting the government to expedite the SMEs business community by utilizing the industry era 4.0 in the Non-Bank Financial Industry sector.